Ecology and conservation of the Sirenia : dugongs and manatees - Marsh, H. (Helene), 1945-; O'Shea, Thomas J.; Reynolds, John Elliott, 1952-; Cambridge eBooks (Cambridge : Cambridge University Press, 2011)
Dugongs and manatees, the only fully aquatic herbivorous mammals, live in the coastal waters, rivers and lakes of more than 80 subtropical and tropical countries. Symbols of fierce conservation battles, sirenian populations are threatened by multiple global problems. Providing comparative information on all four surviving species, this book synthesises the ecological and related knowledge pertinent to understanding the biology and conservation of the sirenia. It presents detailed scientific summaries, covering sirenian feeding biology; reproduction and population dynamics; behavioural ecology; habitat requirements and threats to their continued existence. Outlining the current conservation status of the sirenian taxa, this unique study will equip researchers and professionals with the scientific knowledge required to develop proactive, precautionary and achievable strategies to conserve dugongs and manatees. Supplementary material is available online at: www.cambridge.org/9780521888288.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Sirenia; Electronic books